Mental Health Symptoms, Binge Drinking, and the Experience of Abuse During the COVID-19 Lockdown in Mexico - Morales Chainé, Silvia; López Montoya, Alejandra; Bosch Maldonado, Alejandro; Beristain Aguirre, Ana; Robles García, Rebeca; Garibay Rubio, Carlos Rodrigo; Astudillo García, Claudia Iveth; Lira Chávez, Isaura Angélica; Rangel Gómez, María Gudelia (Frontiers in Public Health, 2021)
Background: The health crisis associated with the COVID-19 pandemic is causally linked to negative mental health symptoms in the same way as other diseases such as Ebola. Objective: The purpose of this paper is to describe the relationship between mental health symptoms, binge drinking, and the experience of abuse during the COVID-19 lockdown. Method: We surveyed 9,361 participants, all Mexican, with an average age of 33 years old (SD = 10.86). In this group of people, we found out that 59% were single (5,523), 71% were women (6,693). Forty-six percentage were complying with lockdown procedures (4,286), 50% were partially complying (4,682), and 4% were not complying at all (393). The invitation to participate was open from April 24th to April 30th during the second stage of the pandemic in Mexico, in 2020, characterized by voluntary complete lockdown staying at home. Thus, we used a cross-sectional online survey design to assess mental health risk factors related to the COVID-19 pandemic. The survey was available on a WebApp designed by Linux®, PHP®, HTML®, CSS®, and JavaScript®. We calculated descriptive and inferential analysis to describe the mental health average distribution as a function of the lockdown, binge drinking, and experience of abuse. To calculate the reliability and validation of the subscales, we used Cronbach's Alpha and Factor Loading. We run the confirmatory factor loading analysis, and we described the relationship between each latent variable and its item factor load, obtained through structural modeling equations, derived from 179 iterations and 207 parameters (t[1,171] = 28,079.418, p < 0.001). We got a CFI of 0.947, a TLC of 0.940, an RMSEA of 0.049 (0.049–0.050), and an SRMR of 0.048. Findings: The results indicated that reported attitudes such as avoidance, sadness, withdrawal, anger, and anxiety were associated with acute stress, which was linked to an anxiety condition caused by uncertainty about achieving or maintaining overall good health. Discussion and Prospects: People in lockdown mentioned a sudden increase in alcohol consumption. They lived episodes of physical and emotional abuse, in contrast with those who stated that they did not go into lockdown or consume alcohol, or experienced abuse. Limitations: Further studies should diagnose mental health conditions as part of the impact of COVID-19, ensure their follow-up, and assess the effect of providing remote psychological care. There is a need to explore methods to curb the increase in the number of people affected by post-traumatic stress disorder.